Removal of heavy metals using different polymer matrixes as support for bacterial immobilisation - Pires, Carlos; Marques, Ana P. G. C.; Guerreiro, Antonio R.; Magan, Naresh; Castro, Paula M. L. (Elsevier, 2011)
Great attention is focused on the microbial treatment of metal contaminated environments. Three bacterial strains, 1C2, 1ZP4 and EC30, belonging to genera Cupriavidus, Sphingobacterium and Alcaligenes, respectively, showing high tolerance to Zn and Cd, up to concentrations of 1000ppm, were isolated from a contaminated area in Northern Portugal. Their contribution to Zn and Cd removal from aqueous streams using immobilised alginate, pectate and a synthetic cross-linked polymer was assessed. In most cases, matrices with immobilised bacteria showed better metal removal than the non-inoculated material alone. For the immobilisation with all the polymers, 1C2 was the strain that increased the removal of Zn the most, whereas EC30 was the most promising for Cd removal, especially when combined with the synthetic polymer with up to a ca. 11-fold increase in metal removal when compared to the polymer alone. Removal of individual metals from binary mixtures showed that there was differential immobilisation. There was greater removal of Cd than Zn (removals up to 40% higher than those showed for Zn). The results show that metal contaminated environments constitute a reservoir of microorganisms resistant/tolerant to heavy metals that have the capacity to be exploited in bioremediation strategies.Capsule immobilisation of bacteria in the naturally occurring alginate and pectate and in a synthetic cross-linked polymer increased the Zn and Cd removal abilities from single and binary contaminated waters; the applications with the synthetic polymer were the most promising for Cd and Zn removal in single and binary mixtures.